Strategi Guru dalam Pembentukan Karakter Peserta Didik di SMA Muhammadiyah Kupang - Yeti Zel Vida Malaikokal; Ahmad Atang (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2023)
This study aimed to determine the teacher's strategy in shaping the character of students, and inhibiting factors of the teacher's strategy in forming the character of students at SMA Muhammadiyah Kupang. This study used a qualitative method. The subjects of this study were teachers and students. The technique of data collection was done by means of observation, interviews, and documentation. The data analysis technique used data reduction, data presentation, and conclusion. The results of the research are the teacher's strategy in forming the character of students has been proven quite well; (a) understanding included the ability of teachers to design lessons, assess the process of learning outcomes and shape the character of students, (b) habituation included the habit of working on questions on time and teachers instil disciplined habits, (c) teachers set a good example, positive advice, and reprimand to form good character towards students. The inhibiting factors for the teacher's strategy in shaping the character of students at SMA Muhammadiyah Kupang are internal factors in the form of talents, interests, and character, while external factors in the form of family and environmental factors.